PENGARUH MEDIA PEMBELAJARAN BERBASIS AUDIO VISUAL TERHADAP PRESTASI BELAJAR PKn MATERI HARMONISASI PEMERINTAH PUSAT DAN DAERAH PESERTA DIDIK KELAS X MAN SIABU - Yusmiati Yusmiati; Nuralina Nuralina (Universitas Muhammadiyah Tapanuli Selatan, 2020)
The formulation of the problem in this study is whether there is an effect of audio-visual based learning media on learning achievement of Civics material harmonization between central and local government class X MAN Siabu. While the research objective was to see the effect of audio-visual based learning media on learning achievement of PPKn material on Harmonization of the central and regional government for class X MAN Siabu students. This type of research is descriptive research, namely research that provides a picture of the second variable. The second variable is audio-visual based learning media (variable X), learning achievement (variable Y). The approach used is the library research approach, and the field research approach is the approach taken by the researcher directly using a questionnaire or test. The population in this study were all class X MAN Siabu as many as 288 students consisting of X MIA 1 to X MIA 4, and X IIS 1 to X IIS 4. While the sample of the study was 43 students, who were taken randomly. Hypothesis testing technique in this research is